2022
DOI: 10.1186/s12711-022-00696-9
|View full text |Cite
|
Sign up to set email alerts
|

Genomic diversity and signatures of selection in meat and fancy rabbit breeds based on high-density marker data

Abstract: Background Domestication of the rabbit (Oryctolagus cuniculus) has led to a multi-purpose species that includes many breeds and lines with a broad phenotypic diversity, mainly for external traits (e.g. coat colours and patterns, fur structure, and morphometric traits) that are valued by fancy rabbit breeders. As a consequence of this human-driven selection, distinct signatures are expected to be present in the rabbit genome, defined as signatures of selection or selective sweeps. Here, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 86 publications
7
24
1
Order By: Relevance
“…The role of this gene is, however, not completely well defined yet. In another study that involved Checkered Giant rabbits (Ballan et al, 2022 ), using F ST parameters we confirmed the signature of selection in this gene region. Therefore, it is quite remarkable that two independent types of analyses (i.e.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The role of this gene is, however, not completely well defined yet. In another study that involved Checkered Giant rabbits (Ballan et al, 2022 ), using F ST parameters we confirmed the signature of selection in this gene region. Therefore, it is quite remarkable that two independent types of analyses (i.e.…”
Section: Discussionsupporting
confidence: 78%
“…It will be also interesting to compare the results of the two methods that we have applied thus far to identify signatures of selection (i.e. the ROH island method described in this study and the F ST method previously reported; Ballan et al, 2022) with other methods that can be implemented using the same SNP datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ERVs were found to function as species-specific enhancers in the germline gene expression, influencing spermatogenesis and possibly contributing to speciation ( 48 ). NTRK2 , a gene associated with body weight in humans and mice ( 49 ), was found to have two copies on the gyrfalcon’s W chromosome. While it has gametolog on the Z chromosome, the two W-linked copies may suggest a possible overexpression in females that may contribute to the reverse sexual dimorphism (RSD) known in falcons, where females are larger than males.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, hair structure can also be used to distinguish distinct rabbit breeds. Ballan et al (2022) conducted selection signature studies using F ST analysis (with single-breed analysis and analysis of the group of breeds) in three commercial and 12 fancy rabbit breeds to explain the phenotypic variability between these breeds. The studies revealed selection signatures in genomic windows containing genes determining coat color (ASIP, MC1R, and TYR) and coat structure (LIPH).…”
Section: Rabbitmentioning
confidence: 99%